A novel milling force model based on the influence of tool geometric parameters in end milling. (September 2018) - Zhang, Xianglei; Zhang, Jing; Zhou, Hongming; Ren, Yan; Xu, Mingming
A novel milling force model for cutting aviation aluminum alloy 7075 using carbide end mill is established in this article. A two-dimensional end-milling model is set up to investigate the influence of tool geometric parameters on milling force with the single-factor analysis. The relationship between milling forces and tool geometric parameters is obtained by nonlinear regression fitting method. Based on the existing empirical model of milling force, quadratic polynomial factor is taken into consideration to explore the influence of tool geometric parameters on milling force. Thus, a novel milling force model is built up which includes tool geometric parameters and milling parameters. The coefficients of the novel model are identified by the direct method and the loop method. The precisions of the coefficients obtained by the two methods are compared between prediction values and experiment values. After comparison, the model whose coefficients are obtained by loop method has higher prediction ability. End-milling experiments were carried out to verify the prediction accuracy of the novel milling force model. The result shows that the novel model of milling force has high accuracy in prediction. The method of building the milling force model proposed in this article can be applied to other types of milling cutter.